Influence of internet and social media presence on small, local banks' market power - Dariusz Filip; Krzysztof Jackowicz; Lukasz Kozlowski (Baltic Journal of Economics, 2017)
We study the impact of Internet and social media presence on the market power of small, local banks in Poland. We observe that small banks, which generally embraced new distribution and communication channels considerably later than the large commercial banks, had to forego a portion of their market power to defend market shares or reach new customers. The size of the market power sacrifice was greater when small banks competed against numerous banks within their local markets and particularly substantial when they were outnumbered mostly by large commercial banks.
Keywords: D4; G21; L1; 330; Small banks; market power; internet; social media; local banking markets